Coherent Cooperative Control of New Energy Power System Microgrid Cluster Based on Discrete Coherence Algorithm - Hu, Yuyang; Pan, Lianrong; Wei, Xin; Yang, Xiao; Yuan, Shangbin (Journal of physics. Conference series, 2025)
Conventional new energy power system microgrid group consistency cooperative control method mainly uses adaptive frequency sag control technique for control frequency coupling, which is easily affected by the dynamic adjustment of the sag coefficient, resulting in high cooperative control cost, therefore, a new new new energy power system microgrid group consistency cooperative control method based on discrete consistency algorithm needs to be designed. That is, the discrete consistency algorithm is used to generate a new energy power system microgrid group consistency cooperative control strategy, and the new energy power system microgrid group consistency cooperative control architecture is designed, so as to realize the power system microgrid group consistency cooperative control. The experimental results show that the real-time power regulation cost, cumulative operation cost and cumulative transmission loss cost of the designed new energy power system microgrid group consistency cooperative control method are lower, which proves that the designed new energy power system microgrid group consistency cooperative control method has a better control effect, lower control loss, and has a certain economic value, and makes a certain contribution to the solution of the current power allocation problem of the microgrid group.